2021
DOI: 10.5812/amh.111598
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Characteristics of Patients Infected with Coronavirus Disease-2019 (COVID-19): A Retrospective, Observational Study from Iran

Abstract: Background: Management of Covid-19 patients is key to control the pandemic. In this line, access to chest Computed Tomography (CT) scan findings and investigating changes during initial diagnosis until recovery is of crucial importance. Objectives: The present study aimed to investigate the chest CT-scan findings of patients with a definitive diagnosis of Covid-19 in Guilan, Iran. Methods: In this retrospective study, 1000 patients with a definitive diagnosis of Covid-19, from 20 April to 30 July 2020, were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Newborns with bronchopulmonary dysplasia, prematurity, severe malnutrition, immunodeficiency, and respiratory disorders also need more careful COVID-19 exposure and disease management, as do newborns with congenital heart disease. 13 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newborns with bronchopulmonary dysplasia, prematurity, severe malnutrition, immunodeficiency, and respiratory disorders also need more careful COVID-19 exposure and disease management, as do newborns with congenital heart disease. 13 14…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that infants had less severe symptoms, a milder clinical course, and rarely need for hospitalization. 13 A review of clinical characteristics of COVID-19 showed that 92% of infants and children were asymptomatic. Fever, cough, respiratory distress, feeding intolerance, vomiting, diarrhea, cyanosis, and tachycardia are the most common clinical symptoms in the neonatal age group.…”
Section: Discussionmentioning
confidence: 99%
“…Según el Instituto Ecuatoriano de Estadísticas y Censos (2021), en el año 2020 se han producido 191 muertes maternas, con una tasa de mortalidad materna de 57.6 por cada 100.000 nacidos vivos, sin indicar la principal causa de muerte; mientras que en la gaceta de la semana epidemiológica del Ministerio de Salud Pública, N° 53 del año 2020, se registra 163 muertes maternas, siendo la segunda causa de muerte materna el COVID-19, luego de los trastornos hipertensivos del embarazo (Ministerio de Salud Pública del Ecuador, 2020). Panahi et al (2020), afirma que las mujeres tienen mayor riesgo de presentar complicaciones en el embarazo, al infectarse con el virus Sars CoV 2, como dificultad respiratoria y parto prematuro, llegando inclusive a la muerte materna. En el estudio realizado por (Cupul-Uicab et al, 2021) se observó que en las gestantes con COVID-19, presentaron mayor ingresos a cuidados intensivos y uso de ventilación mecánica invasiva.…”
Section: Complicaciones Maternasunclassified
“…COVID-19 is an infectious disease that was declared a public health emergency of international concern by the WHO [54]. Their main concern is whether breastfeeding by mothers infected with COVID-19 is safe, and whether the virus or antibodies can be transmitted from mother to baby through milk [55].…”
Section: Pregnancy and Breastfeeding During The Covid-19 Pandemicmentioning
confidence: 99%